ANALISIS STUDI KEPUTUSAN PEMAKAIAN JASA PENERBANGAN GARUDA INDONESIA (Studi Pada Penumpang Garuda Indonesia Keberangkatan rute dari Semarang) - Pangesti, Made Ayu Ayu Hosananing; Tri Astuti, Sri Rahayu (Faculty of Economics and Business Diponegoro University, 2015)
This study aimed to examine the effect of perception of quality and sales promotions on brand awareness ; to examine the association of the brand , the quality perception and sales promotion of the decision to use of services and to examine the effect brand awareness to decision to use of services. The background problem of this study is the decreasing number of top brand index Garuda Indonesia from the last three years , the realization of the target market share of Garuda Indonesia in 2010 and 2013 did not meet the target in the desired and Garuda Indonesia is still not able to master the market share of flying the domestic departure of Semarang.This research is using the questionaire methode to collect the data from 100 sample respondent, the sampling technic used is accidental sampling and data analysis used in this research is multiple linear regression method.The results show Â ( 1 ) the perception of quality and sales promotion significant positive effect on brand awareness , ( 2 ) brand association , perception of quality, brand awareness and sales promotion significant positive effect on the decision use of the services.